User Experience Evaluation and Recommendation for Persada Hospital’s Information System - Taufiq, Milkhatussyafa'ah; Pandya, Davin Nayaka; Kurniawan, Calvin Farrellino; Suryadharma, Doddy (Media Jurnal Informatika, 2023)
Persada Hospital’s information system is a website that has many features available to the user, such as doctor’s schedules, facilities, and many more. The main determinants of how well this website is used are its user interface and user experience (UI/UX), reliable functionality, and usability. Therefore, to always provide a positive user experience, the web developer needs to pay attention to these aspects. In this paper, we evaluate the user experience based on a tool called User Experience Questionnaire (UEQ). Based on our research, Persada Hospital’s information system has a good score with some exceptions, namely the speed and usualness of the website. Overall, Persada Hospital’s information system has a good UX. However, we have adjusted our ideas to improve the hospital website's user design. Our study has shown that increasing the overall attractiveness and innovativeness of the website is critical for creating a favorable user experience.